2016
DOI: 10.3164/jcbn.15-147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflavones on lipid and apolipoprotein levels in patients with type 2 diabetes in Heilongjiang Province in China

Abstract: In this study, we examined the association between soy isoflavones and lipid profiles, apolipoprotein levels in patients with type 2 diabetes in China. The study population was composed of 120 cases (80 women with type 2 diabetes and 40 healthy women). Objects in treatment group received isoflavones 435 mg/day for 2 months, then lipid profiles were analyzed by the colorimetry method and apolipoprotein levels were determined by immune turbidimetric method. And all the indexes were determined after oral glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…In fact, it has been reported that supplementation of soy isoflavones is effective for improving lipid profiles and apolipoprotein levels in patients with type 2 diabetes. ( 31 )…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that supplementation of soy isoflavones is effective for improving lipid profiles and apolipoprotein levels in patients with type 2 diabetes. ( 31 )…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, the consumption of isoflavone-rich functional foods is highly recommended owing to the potential health protection against some aging-associated diseases such as cardiovascular disease, osteoporosis, hormone-related cancer, and cognitive impairment ( Gilbert and Liu, 2013 ; Vitale et al, 2013 ; Chi et al, 2016 ) ( Figure 3 ). Even though isoflavones present in a variety of plant-derived products such as cereals, potatoes, vegetables, and fruits, the richest sources in the human diet are soy-derived foods ( Kraszewska et al, 2007 ).…”
Section: Role Of Isoflavones In Human Healthmentioning
confidence: 99%
“…With regard to lipoproteins, a meta-analysis of 38 objects showed that soy supplementation results in an improvement in total and LDL-C [20], however, the benefit was mainly limited to subjects with very high pretreatment lipids. Furthermore, supplementation with 435 mg/day of isoflavone exerted a favorable effect on the total cholesterol, LDL-C levels and the ratio of apolipoprotein A1/apolipoprotein B in the blood of Chinese type 2 diabetic women [21]. On the basis of these studies, the regulatory effect and pathways of soybean bioactive substances on hyperlipidemic postmenopausal women were further investigated by measuring the protein and mRNA expression levels of LDLR, LXRα, and ABCG1 in hyperlipidemic postmenopausal women using western-blot and quantitative real-time polymerase chain reaction (qRT-PCR), respectively.…”
Section: Introductionmentioning
confidence: 99%